2000
DOI: 10.1108/13527600010797084
|View full text |Cite
|
Sign up to set email alerts
|

Cultural diversity in learning: developing effective learning for South Asian hospitality management students

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…Various researchers have cited differences in learner expectations as being a culturally bound phenomenon, see, for instance, passivity in the learning of Asian students (Maxwell et al 2000), and differences between European and Asian students' motivation to study (Selvarajah 2006). A study on Arab education (World Bank 2008) found that learners are passive recipients of knowledge and lack applied learning in ''the higher-order cognitive skills such as flexibility, problem solving and judgment'' (p. 89).…”
Section: Literature Review the Context For The Introduction Of Learnimentioning
confidence: 99%
“…Various researchers have cited differences in learner expectations as being a culturally bound phenomenon, see, for instance, passivity in the learning of Asian students (Maxwell et al 2000), and differences between European and Asian students' motivation to study (Selvarajah 2006). A study on Arab education (World Bank 2008) found that learners are passive recipients of knowledge and lack applied learning in ''the higher-order cognitive skills such as flexibility, problem solving and judgment'' (p. 89).…”
Section: Literature Review the Context For The Introduction Of Learnimentioning
confidence: 99%
“…In addition, few studies that have examined coping mechanisms employed by international student samples have attempted to identify resources available to international students and their ability and propensity to make use of available social resources. However, the availability of counseling facilities at host universities, informal sources of social support, and financial resources all have been identified as significant resources for international students to facilitate their ability to cope with stressors during the process of adjusting to new educational settings (Constantine, Okazaki, & Utsey 2004;Maxwell et al, 2000;Misra et al, 2003;Mori, 2000;Randall, Naka, Yamamoto, Nakamoto, Arakaki, & Ogura, 1988). Utilization of these resources to develop problem-oriented coping mechanisms was found to be related to better adjustment outcomes.…”
Section: Coping Mechanismsmentioning
confidence: 99%
“…Comparable transitions between educational institutions are made more challenging for international students since the transitions they experience often involve additional environmental demands including: changes in the location of the educational institution, increases in demands for language proficiency, changes in availability of specific family and social support systems, and added financial burdens. Specific features of the educational system of the United States have also been reported by researchers to influence significantly international students' adjustment (Maxwell, Adam, Pooran, & Scott, 2000). In contrast to the commonly passive content-based teaching styles of several foreign pedagogical systems (e.g., the Southeast Asian system), the more active teaching styles of Western education systems demand more student participation in the classroom.…”
Section: Pedagogical Issues and Academic Stressorsmentioning
confidence: 99%
See 2 more Smart Citations